How does FinTech investment affect banks' returns and risks? Evidence from China’s banks - Yang, Suyu (2022)
The whole term of FinTech is "Financial Technology". Rapid FinTech developent has had a significant and far-reaching impact on China's banking sector. The paper uses data from 48 Chinese banks from 2009 to 2019 to conduct theoretical analysis and empirical study. To explore the effect of FinTech investments on banks' returns and risks, the paper uses fixed-effects regression models on static panel data. The specific findings are as follows: First, FinTech investment positively affects banks' returns in terms of profitability (return on total assets and cost-to-income ratio). Secondly, FinTech investment weakens bank risk in terms of the non-preforming loan ratio and the capital adequacy ratio. Third, the paper further suggests that the impact is moderated by macroeconomic environment, which can be different under different measures. Fourth, there will also be heterogeneity in the effect of FinTech investment on returns and risks across banks. That is, the impact of FinTech investment on the returns and risks is different between state-owned and non-state-owned banks, and between national and local banks. The paper suggests that banks should pay attention to the integration of FinTech and banking, and that bank managers should also be fully aware of the risk that FinTech may bring. In addition, when considering FinTech investments, they should adjust their investment strategies according to the macro environment.